(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Cloud computing is the most recent arrival to the world of IT infrastructure. Also, Cloud Computing is one of the most emerging areas in the field of research and development. It allows companies to maximize the utilization of their resources and consequently raise their performance. The main benefit of Cloud Computing is the significant rise in the efficiency of executing their various business plans. It provides large applications with powerful computing parameters like scalability, adaptability, reliability, etc. This paper includes the study of various existing heuristic approaches used to improve different parameters. In cloud computing, there are large numbers of problems while you are going for scheduling requests from users. However in practice there is only need of solving the issue of efficiently even if not optimal. Keywords - Cloud Computing, Heuristic, Load Balancing